Prevalence of HIV infection among transgender women and travestis in Brazil: data from the TransOdara study - Inês Dourado; Laio Magno; Beo Oliveira Leite; Francisco Inácio Bastos; Jurema Corrêa da Mota; Maria Amélia de Sousa Mascena Veras; Marcia Jorge Castejon (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective The aim of this study was to investigate the prevalence of human immunodeficiency virus (HIV) infection among transgender women and travestis and to analyze factors associated with HIV infection in Brazil. Methods TransOdara was a cross-sectional study on sexually transmitted infections among transgender women and travestis in five Brazilian cities between 2019 and 2021. Self-identified transgender women and travestis aged ≥18 years were recruited using respondent-driven sampling, completed an interviewer-led questionnaire, and provided samples to detect HIV. The outcome was the result of the rapid antigen testing for HIV. Adjusted prevalence ratios (aPR) and 95% confidence intervals (95% CI) were obtained using Poisson regression with robust variance. Results Overall, this population was found to be especially vulnerable, with high levels of unstable housing and engagement in informal work. They usually resort to transactional sex as their main working activity. Half of them earned less than the Brazilian minimum wage, which characterizes a poor population living in dire conditions. The overall HIV prevalence was 34.40%. In the final model, the variables associated with the HIV prevalence were as follows: to be 31 years old or older, not studying at the moment they were interviewed, to be unemployed, and engaged in lifetime transactional sex. Conclusion We found disproportionately high HIV prevalence among transgender women and travestis, compared with a low prevalence among respective segments of Brazil's general population, which highlights the context of vulnerability in this population. The data point to the urgency for intensification and expansion of access to HIV prevention and strategies to stop discrimination in health care (among other services and contexts) and provide comprehensive services for this population.